2006
DOI: 10.1590/s0021-75572006000300014
|View full text |Cite
|
Sign up to set email alerts
|

Quem são as crianças que se sentem gordas apesar de terem peso adequado?

Abstract: Objective: To measure the prevalence of children with adequate weight who feel fat and to examine the factors associated with this perception.Methods: Cross-sectional study with 901 schoolchildren aged 8-11 years selected by cluster sampling. The children had their weight and height measured, and answered a questionnaire that included a self-esteem scale and questions on self-perception of weight, and perception of parents and friends expectations regarding the childs weight.Results: The prevalence of children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
7

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
1
4
0
7
Order By: Relevance
“…Most girls wanted to lose weight, whereas boys were more likely to desire weight gain. These results are consistent with those reported in other studies, which show that, regardless of nutritional status, women generally seek a slimmer figure (23) whereas men want stronger bodies (16,22) . According to Kostanski et al, the issue of body image dissatisfaction affects both genders, but not in the same manner; therefore, prevention and mitigation strategies should target each gender independently (24) .…”
Section: Discussionsupporting
confidence: 92%
“…Most girls wanted to lose weight, whereas boys were more likely to desire weight gain. These results are consistent with those reported in other studies, which show that, regardless of nutritional status, women generally seek a slimmer figure (23) whereas men want stronger bodies (16,22) . According to Kostanski et al, the issue of body image dissatisfaction affects both genders, but not in the same manner; therefore, prevention and mitigation strategies should target each gender independently (24) .…”
Section: Discussionsupporting
confidence: 92%
“…The present results showed that all adolescents were prone to body image dissatisfaction, irrespective of age. Within this context, the literature demonstrates that body dissatisfaction can manifest throughout all phases of life, including children 20 , adolescents 28 , adults 21 , and the elderly 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Variations in prevalence rates have also been reported for small towns, with rates ranging from 63.9% to 85% 14,19 . With respect to age, body image dissatisfaction is observed among all age groups 20,21 . Adolescents are constantly worried about their weight, seeking a beauty ideal, and the lack of acceptance of the body makes them feel excluded from society 22 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Estudos com populações européias, norte-ameri- Considerando os valores médios do grupo, foi verificada uma tendência dos meninos idealizarem silhuetas maiores e as meninas silhuetas menores, confirmando os dados apresentados pela literatura. 19,20 Esse comportamento também foi identificado por outros estudos que discutem a influência social e da mídia, que levam os meninos a desejarem uma silhueta maior, indicando corpos mais fortes, e…”
Section: A S S O C I a T I O N ( A N E P ) P Re V A L E N C E R A Tunclassified